Final answer:
To find f(-1) for the given function f(x) = x^2 - 6x + 3 / (x - 1), substitute -1 for x and simplify the expression to calculate the result. The result of f(-1) is -5, which corresponds to option A.
Step-by-step explanation:
The student has asked to find the value of the function f(x) when x is equal to -1. The function is given as f(x) = x2 − 6x + 3 / (x − 1). To find f(-1), we substitute x with -1 in the equation and perform the necessary arithmetic operations.
First, we replace x with -1:
f(-1) = (-1)2 − 6(-1) + 3 / ((-1) − 1)
This simplifies to:
f(-1) = 1 + 6 + 3 / (-1 - 1)
Further simplifying, we get:
f(-1) = 10 / -2
Finally, we can see that f(-1) equals to:
f(-1) = -5
Therefore, the correct answer is A) − 5.